The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1093/jmcb/mjab047
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the PTM codes of the tumor suppressor p53

Abstract: The genome guardian p53 functions as a transcription factor that senses numerous cellular stresses and orchestrates the corresponding transcriptional events involved in determining various cellular outcomes, including cell cycle arrest, apoptosis, senescence, DNA repair, and metabolic regulation. In response to diverse stresses, p53 undergoes multiple posttranslational modifications (PTMs) that coordinate with intimate interdependencies to precisely modulate its diverse properties in given biological contexts.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 113 publications
0
20
0
Order By: Relevance
“…Cancer cells acquire unique metabolic characteristics to ensure their survival and proliferation (DeBerardinis, 2008). Recent studies have been shown that p53 regulates metabolic traits of cells in addition to its role as a tumor suppressor protein (Wen and Wang, 2021), but the exact mechanism by which p53 regulates metabolism is still not completely understood. As a compensatory response to protect cells against stress, increased signaling triggered by p53 leads to activation of the PtdIns3K-Akt-MAPK-Ras signaling pathway (Corcoran et al, 2006).…”
Section: P53 Signaling Targets As a Cancer Therapy Via Modulation Of Autophagymentioning
confidence: 99%
“…Cancer cells acquire unique metabolic characteristics to ensure their survival and proliferation (DeBerardinis, 2008). Recent studies have been shown that p53 regulates metabolic traits of cells in addition to its role as a tumor suppressor protein (Wen and Wang, 2021), but the exact mechanism by which p53 regulates metabolism is still not completely understood. As a compensatory response to protect cells against stress, increased signaling triggered by p53 leads to activation of the PtdIns3K-Akt-MAPK-Ras signaling pathway (Corcoran et al, 2006).…”
Section: P53 Signaling Targets As a Cancer Therapy Via Modulation Of Autophagymentioning
confidence: 99%
“…There are crystal structures available for the p53 DNA-binding domain, both the WT, alone or bound to different DNA target sites, some hotspot p53 mutations [ 10 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 ], and the p53 TET domain [ 13 ]. However, there is still a lack of data to fully reveal the structural details of the crosstalk between the different domains, including the intrinsically disordered and heavily post-translationally modified N-ter and C-ter domains [ 10 , 16 , 19 , 24 , 81 , 82 ]. This lack of knowledge represents a severe limitation, as p53 is a highly versatile transcription factor that interacts through a wide range of affinity with many DNA RE-binding sites that can be structurally diverse in their internal organization [ 12 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The transactivation domains are critical for p53 function [ 6 , 17 ] and are located in the amino-terminal sequence (within the first 60 amino acids), a region that is considered to be intrinsically disordered [ 18 , 19 , 20 , 21 ]. Together with the last 30 amino acids in the C-ter, it is subject to several post-translational modifications that impart changes in protein–protein interactions, conformation, subcellular localization, and function to the protein [ 22 , 23 , 24 ]. p53 post-translational modifications were also shown to affect long-range intramolecular interactions between either the N-ter or the C-ter and the DBDs, influencing DNA binding [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Overexpressed LSD1 in cancer cells promotes glucose uptake and glycolytic activity and upregulates the expression of GLUT1 and glycolytic enzymes; however, it strongly downregulates the expression of mitochondrial metabolism-related genes (Luo et al, 2021). Knockdown or pharmacological inhibition of LSD1 can activate the transcriptional activity of the gluconeogenesis genes FBP1 and G6Pase, resulting in increased de novo glucose synthesis and decreased intracellular glycogen content (Wang D. et al, 2022). Inhibition of LSD1 activity in oesophageal cancer cells can significantly reduce the extracellular acidification rate (ECAR) and increase the oxygen consumption rate (OCR) and OCR/ECAR ratio (Kosumi et al, 2016).…”
Section: Energy Metabolism Pathwaymentioning
confidence: 99%
“…LSD1 may contribute to the malignant behaviour of oesophageal cancer by regulating metabolism, glycolytic pathway, and mitochondrial respiration. In addition, LSD1 plays an important role in regulating adaptive thermogenesis and lipid metabolism and may be a novel target for treating obesity (Wang D. et al, 2022).…”
Section: Energy Metabolism Pathwaymentioning
confidence: 99%